Lateral stress and its transmission law caused by operation of a double-wing subsoiler in sandy loam soil - Qin, Kuan; Zhao, Yun; Zhang, Yongzheng; Cao, Chengmao; Shen, Zhougao (Frontiers in Environmental Science, 2022)
Sandy loam soils are widespread and important for agricultural soil use. The lateral stress caused by the loosening shovel of a subsoiler produces lateral disturbances in sandy loam soil, reducing compaction and improving soil structure. To explore the variation and transmission of lateral stress due to the operation of a double-wing subsoiler in sandy loam soil, a lattice of point-type soil sensors was arranged in a soil bin, and the lateral stress generated by subsoiling was measured in the shallow, medium, and deep soil layers. The experimental results show that when the lateral stress generated by the double-wing subsoiler is transferred to the lateral position of different distances.The lateral stress shows a sinusoidal fluctuation law with time, the sine wave frequency range is: shallow (0.366–0.549); middle (0.306–0.494); and deep (0.088–0.501). There were greater fluctuation amplitudes in the transfer process for the shallow and deep soil layers than for the middle layer. Shallow soil had the largest final stable lateral stress (0.1617 N), and middle soil the smallest (0.0733 N). Thus, lateral stress from deep loosening has the greatest effect on shallow soil and the least effect on middle soil. These results indicate that the fluctuating lateral stresses generated by double-wing-subsoiler operation drive a fluctuating soil disturbance that can improve soil structure, and that they are greater for shallow and deep soils than for middle soils.